Does the religious studies expertise need? - Fylypovyč, Ljudmyla Oleksandrivna (Ukrai͏̈ns'ke relihijeznavstvo, 2016)
In the L.Fylypovych’s article «Does the religious studies expertise need?» the basis of the expert activity in the field of religious life sets out, and the main principles of scientific expertising formulates. The aims of expertising is the essential understanding of the modern expressions of functionality of religion and its impact on society and human.